RUANG LINGKUP MAQASID DALAM TAFSIR AL-TAHRIR WA’L-TANWIR - amir, ahmad nabil; Rahman, Tasnim Abdul (Wahana Islamika, 2025)
This paper examines the underlying ideas and scope of maqasid al-syariah (higher objective of Islamic law) propagated by Muhammad al-Tahir ibn ‘Ashur (1879-1973) in his seminal work, Tafsir al-Tahrir wa’l-Tanwir. It looks into the connection between his interpretation and the instrumentality of the verses and its scriptural paradigm designed to bring forth the ideas and doctrines of maqasid and maslahah (common good) in his tafsir. The study is technically based on qualitative method in the form of analytical and logical reasoning. The finding concludes that the Tafsir al-Tahrir wa’l-Tanwir was structurally constructed based on the principle of maqasid al-shariah that ideally expounded its rational and philosophical basis. Its legal formulation was based on the Islamic reference of the Qur’an, hadith, maqasid al-Qur’an (higher objective of the Quran), reason and  analogical reasoning and premises. Ibn Ashur’s work had broadly influence the intellectual progress and development of ijtihad oriented toward maqasid as well as dynamic understanding and consciousness of the spirit of law (syariah) in the modern context.